الصيرفة الالكترونية بين جدلية الاستفادة من الثورة المعلوماتية و إخفاقات التطبيق (المجلة العراقية للعلوم الاقتصادية, 2018)
the banking institutions have become providing services to customers and business enterprise in remoting, and so electronic transfers of funds have been consistent reality in all parts of the world, in addition to some technical characteristics of the internet, this has resulted in raising concerns of bankers and supervisory authorities alike, in terms of increasing and diversity of the risks associated with this development, supervisors and bankers agree that the foundations and principles that apply to the traditional banking business are applicable to electronic banking operations, however all the rapid change in technology and the degree of the bank on technology providers have led to change and amplify traditional banking risks, this indicates that there are specific areas need further guidance by the supervisory authorities in order to push the over all framework of the electronic banking operations.